Yusif Sayigh : Arab Economist, Palestinian Patriot: A Fractured Life Story. - Sayigh, Rosemary (The American University in Cairo Press, 2015)
An acclaimed economist and lifelong Palestinian nationalist Yusif Sayigh (1916-2004) came of age at a time of immense political change in the Middle East. Born in al-Bassa, near Acre in northern Palestine, he was witness to the events that led to the loss of Palestine and his memoir therefore constitutes a vivid social history of the region, as well as a revealing firsthand account of the Palestinian national movement almost from its earliest inception. Family and everyday life, co-villagers, landscapes, pleasures, outings, schooling, and political figures recreate the vanished world of Sayigh.